A Meta-Analysis of Single-Case Research on Embedding Interests of Individuals With Autism Spectrum Disorder. (September 2020) - Ninci, Jennifer; Neely, Leslie C.; Burke, Mack D.; Rispoli, Mandy; Vannest, Kimberly J.; Willson, Victor; Ulloa, Paula
Restricted interests of individuals with autism spectrum disorder (ASD) can act as a barrier to learning important life skills. Embedding the interests of individuals into their learning environment can act to establish motivation to participate. A meta-analysis of 20 single-case studies on embedding interests of individuals with ASD was conducted to determine overall effects and potential moderating variables. Data were aggregated across domains of variables including dependent variables, participant characteristics, and learning contexts. The correlation between self-stimulatory or ritualistic behaviors and primary outcomes was evaluated. Publication bias and consistency of the Tau/Tau- U nonoverlap effect size with visual analysis were tested via moderator analyses. The literature suggests that embedding interest for learners with ASD can either be beneficial or distractible. Effects ranged from negative to strong, with several moderators identified. Practitioners should take caution when using this intervention with students who display self-stimulatory or ritualistic behaviors when their interests are present.